From Islamism to Neo-Islamism: Political Exegesis in Sayyid Quṭb and Majd Makkī - Abu Sufyan; Mohammad Yunus; Ibnu Burdah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2025)
This article examines the political and ideological dimensions of contemporary Sunni Qur’anic exegesis through a comparative analysis of Sayyid Quṭb and Majd Makki. It focuses on Fī Ẓilāl al-Qur’ān and al-Mu‘īn ‘alā Tadabbur al-Kitāb al-Mubīn to explore how each scholar articulates the relationship between scripture and political order. The study employs a qualitative library-based approach, using comparative content analysis to examine key themes, interpretive strategies, and socio-political contexts shaping both works. The findings show that Quṭb advances a movement-oriented hermeneutics (manhaj ḥarakī) that frames the Qur’an as a basis for systemic resistance against secular authority through the concept of ḥākimīyah. In contrast, Makki develops a contemplative (tadabbur-based) approach that increasingly incorporates themes of democracy, pluralism, and anti-authoritarianism, particularly in response to the Syrian revolution and its digital discourses. This study argues that the contrast between the two reflects a broader shift in Sunni political exegesis from ideological, system-driven Islamism toward a more pragmatic and context-responsive neo-Islamism. It contributes to the study of religion and politics by demonstrating how Qur’anic interpretation functions as a dynamic site of ideological negotiation and political praxis in the modern Muslim world.